The community knowledge, awareness, and practices influencing transmission of toxoplasmosis in Mbeya District, Tanzania (Journal of Ideas in Health, 2023)
Background: Toxoplasmosis caused by Toxoplasma gondii is an important but neglected zoonotic disease of global distribution. The study aimed at evaluating community knowledge, awareness, and practices linked to transmission and control of the disease among the residents of urban and peri-urban areas of Mbeya District, Tanzania. Methods: A cross-section study was conducted from January 2022 to March 2022 in the Mbeya district. A semi-structured questionnaire was self-administered to gather information on social demographic characteristics, knowledge, and risk behaviors related to toxoplasma infection, chi squire was employed to test the difference where p-value < 0.05 was considered statistically significant.Results: A total of 100 respondents were recruited. The majority (38.0%) of the respondents were aged 26 - 35 years and (49.0%) had attained primary education. The average mean age was 35.6 (+ 11.5 SD), 57% were male while 43.0% were female. Only 22 percent of the respondents were aware of toxoplasmosis and among them, 10 percent were aware of the clinical manifestations of the disease and 20 percent knew the mode of the disease transmission. Identified risk practices include lack of deworming in cats (81.0%), outdoor cats management (60.0%), disposal of cats' faces in gardens (36.0%), use of cats in controlling rodents (41.0%), and not wearing gloves during gardening (77.0%). Children are noted to be at the highest risk of contracting the disease as they are greatly involved in caring for cats. (49.0%). The knowledge of the disease was found to be associated with sex (males) p value= of 0.041, occupation (medical employees) p-value =0.002, and high level of education of the respondents' p value =0.000.\.Conclusion: The study revealed a low level of knowledge of the participants and practiced risky behaviors for disease transmission. Thus, we recommend to relevant authorities to offer education to the community concerning Toxoplasmosis.